Case Series: Optometric Approach to Vision-Related Concussion Symptoms, Diagnosis, and Management. - Rutenberg, Zuzana; Eichler, Rachel; Gantz, Liat (Optometry & Visual Performance, 2026)
Background: Sport-related concussions frequently result in persistent visual dysfunctions, including accommodative, binocular, oculomotor, and oculo-vestibular impairments. These deficits can significantly impact quality of life and are often overlooked in standard eye examinations. Optometric vision therapy offers targeted rehabilitation to address these dysfunctions. This case series highlights the benefit of vision therapy in three female patients with sport-related concussions referred for visual evaluation and treatment long after the concussion was sustained. Case Reports: Three patients (ages 20, 27, and 34) with persistent visual symptoms years after one or more concussions were previously examined by eye care providers, yet visual complaints remained unresolved. Each underwent a comprehensive binocular vision assessment revealing various combinations of accommodative excess (patients 1, 2, 3) or insufficiency (patient 2), fusional vergence dysfunction (patients 2, 3), oculomotor deficits (patients 1, 2, 3), and vestibulo-ocular dysfunction (patients 1, 2, 3). Patients completed 11-12 sessions of individualized vision therapy, supplemented by daily home exercises. Following therapy, all patients demonstrated clinically significant improvements in objective findings and selfreported symptoms. Brain Injury Vision Symptom Survey scores improved by 55-59% (34-35 points) across the three cases. Notable functional gains included reduced photophobia, improved reading, less fatigue, and return to academic or physical activities. Conclusions: This case series underscores the essential role of optometrists in post-concussion care. Optometric vision therapy is an effective intervention, even when initiated long after the initial injury. Comprehensive visual function assessment and interdisciplinary collaboration are critical to identifying and managing postconcussion visual dysfunction, ultimately improving patient outcomes.